Technological choice decision-making in Nigeria's public sector - Igwe, B. U. N.; Ndekwu, Eddy Chika; Nigerian Institute of Social and Economic Research (Ibadan, Nigeria : Nigerian Institute of Social and Economic Research, 1985)
This publication focuses on technology in Nigeria's public sector covering various topics like: the Nigerian economy and the nature of problems of technological choice; decision making and technological choice in the public sector; the industrial sector, the federal super-phosphate fertilizer project; health services sector; the agricultural sector; the Kainji Dam project among others.
Includes bibliographical references: p. 145-147.
lje 20/09/2018
Loans
Keywords: Technology assessment; Appropriate technology; Technology and state; Technology - public sector; Nigeria